Isolated 6th cranial nerve palsy with pre-eclampsia: a case report. (18th April 2012) - Turnbull, HL; Harlow, F; Simpson, P
Abstract : Introduction: A 28-year-old primigravida presented to her optician at 33 + /40 with a 4-day history of blurred vision. Her diplopia was consistent with right VI nerve palsy. The obstetricians were consulted about the safety of brain MRI scanning. She was mildy hypertensive with a raised ALT (345 U/L). Hepatitis, autoantibody screen, bile acids and liver scan were normal. Fetal ultrasound was normal. A possible diagnosis of evolving pre-eclampsia (PET) was made. Isolated 6 th cranial nerve palsy with PET has been reported occasionally, but remains rare.1 2 3 The neurology & ophthalmology teams excluded any focal pathology with a normal brain MRI. Serum ANA, ANCA, dsDNA, ACE, RF, C3/C4, and lipids were normal. At 36+/40 she commenced labetolol. Her serum urate, liver function tests (LFTs) and proteinuria were rising, with increasing oedema but stable diplopia. At 37 + /40 her labour was induced and she had a forceps delivery. Labetalol was continued for 3 weeks postnatally. Her LFTs improved after 2 weeks, and her diplopia was almost resolved by 2 months. Conclusion: Cranial nerve palsies are recognised as complications of PET, but VI nerve palsy is very rare. It is thought to be due to compression of the nerve by oedema.